2015
DOI: 10.1007/s11869-015-0379-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigating ozone episodes in Portugal: a wavelet-based approach

Abstract: During the summer season, ozone concentrations regularly exceed the legislation limits in the North of Portugal, namely at Douro Norte monitoring station. The origin of such ozone episodes has been widely reported in several studies although uncertainties regarding its origin still remain. This work intends to investigate how the ozone concentrations measured at the Douro Norte nearest stations, located at west and east directions, are related to those measured at Douro Norte by means of coherence and phase tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…It is observed that the maximum O 3 records occur in the range from 14 to 17 hrs with values ranging from 80 ppb to 160 ppb for the four sites and stations studied; analogous observations can be seen in Refs. [47][48][49][50]. We also note in this Fig.…”
Section: Descriptive Analysissupporting
confidence: 73%
“…It is observed that the maximum O 3 records occur in the range from 14 to 17 hrs with values ranging from 80 ppb to 160 ppb for the four sites and stations studied; analogous observations can be seen in Refs. [47][48][49][50]. We also note in this Fig.…”
Section: Descriptive Analysissupporting
confidence: 73%
“…This hypothesis could also explain an underestimation of O 3 concentrations in the areas downstream of the major precursor sources, as happens in Douro Norte (which is downstream important pollution sources in northwestern Portugal). The high values measured in this station have been widely discussed in several studies, and it is difficult to simulate its behavior [20,58].…”
Section: Observation Data and Model Validationmentioning
confidence: 98%
“…In Portugal, surface O 3 pollution has been characterised in many studies [17][18][19][20][21], especially in the northern [17,[22][23][24] and rural regions [13,25,26]. To complete the study area with more recent data and improve O 3 trends' understanding in Portugal, this study aims to (i) determine the evolution of O 3 levels in Portuguese rural stations, focusing on exceedances to legally imposed levels for human and vegetation protection; (ii) compare the relationship between the O 3 concentrations and one of its precursors (NO x ) for different environments; and (iii) evaluate the effect of meteorological conditions in ozone concentrations.…”
Section: Introductionmentioning
confidence: 99%